2016
DOI: 10.1080/10803548.2016.1196997
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and virtual redesign of a manual handling workstation by computer-aided three-dimensional interactive application

Abstract: The main risk factors were heavy weight and poor control of sugar bags. Virtual redesign can diminish bending and twisting postures, and, therefore, some resulting forces and moments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It was also applied in a sugar factory assessing the bag movement task. A high-risk level was determined [64].…”
Section: Food Product Manufacturementioning
confidence: 99%
“…It was also applied in a sugar factory assessing the bag movement task. A high-risk level was determined [64].…”
Section: Food Product Manufacturementioning
confidence: 99%
“…Sundin and Medbo showed that 3D CAD visualization was successfully used in improving participatory ergonomic work about MMH at a Volvo plant in Sweden [36]. Ziaei et al used rapid upper limb assessment (RULA) to assess the risks of awkward postures and estimate the forces and moments by computer-aided three-dimensional interactive application [37]. Li et al proposed a methodology to use three-dimensional skeletal modeling to imitate workers movement in an actual construction manufacturing plant for lifting task [38].…”
Section: Introductionmentioning
confidence: 99%